A study of the causes of bilateral optic disc swelling in Japanese patients - Iijima K (Dove Medical Press, 2014)
Kei Iijima, Kimiya Shimizu, Yoshiaki Ichibe Department of Ophthalmology, Kitasato University, Kanagawa, Japan Purpose: To investigate the etiology of bilateral disc swelling in Japanese.Methods: Using Kitasato University’s Department of Neuro-Ophthalmology medical records and fundus photographs of the period December 1977 through November 2010, we retrospectively identified 121 outpatients who had been initially confirmed with bilateral disc swelling. Results: The most common cause of the bilateral disc swelling was increased intracranial pressure (ICP) (59%); followed by pseudopapillitis (16%); uveitis (8%); hypertensive retinopathy (5%); bilateral optic neuritis, acute disseminated encephalomyelitis (ADEM) and optic disc drusen (all at 2% each); and leukemia (1%). Unknown etiology accounted for 6% of the cases.Conclusion: Although increased ICP is the most common etiology for bilateral disc swelling, it can also be triggered by a variety of other causes. Pseudopapillitis is the most important progenitor of bilateral disc swelling in Japanese. Keywords: bilateral, disc swelling, papilledema, increased ICP, intracranial pressure